ChemInform Abstract: Pd‐Catalyzed and Copper Assisted Regioselective Sequential C2 and C7 Arylation of Thiazolo[5, 4‐f]quinazolin‐9(8H)‐one with Aryl Halides. Issue 46 (October 2016) - Harari, Marine; Couly, Florence; Fruit, Corinne; Besson, Thierry
Abstract: The synthetically useful title transformation is performed in a convenient one‐pot manner.